No Effect of Long-Term Risedronate Use on Cartilage and Subchondral Bone in an Experimental Rabbit Model of Osteoarthritis - Fernández-Martín, Silvia; Permuy, María; López-Peña, Mónica; Muñoz, Fernando; González-Cantalapiedra, Antonio (Frontiers in Veterinary Science, 2020)
Osteoarthritis (OA) is the most prevalent degenerative joint disease in animals and humans. It is characterized by pain, articular cartilage damage and joint stiffness. It has been suggested that the status of the subchondral bone compartment plays an important role in the initiation and progression of OA. Bisphosphonates have been proposed as a potential disease-modifying treatment for OA, however their effectiveness is not yet clear. Twenty-four male adult New Zealand rabbits were used to evaluate the effects of risedronate on the subchondral bone quality and cartilage degradation in a long-term model of experimentally induced OA. Animals underwent an anterior cruciate ligament transection and partial medial meniscectomy or sham operation in only one knee, which was randomly chosen, using the contralateral as healthy control. Animals were divided into three groups (n = 8): untreated control group and sham surgery control group; both groups received only vehicle; and risedronate group, treated with 2.5 mg orally weekly for 24 weeks. Stifle joints were harvested and scanned using a high-resolution micro-CT to evaluate the subchondral plate and trabecular bone changes. The macroscopic evaluation and histological analysis were determined using an adapted Osteoarthritis Research Society International scoring scheme to assess the cartilage degeneration. The lateral and medial femoral condyle and tibial plateau were evaluated. Additionally, the histological synovial membrane assessment was carried out. Sample analysis showed that the experimental model induced osteoarthritic changes in the operated joints, whereas in sham-operated rabbits, almost no histological changes were observed on articular cartilage surfaces. In terms of macroscopic and histological analyses, risedronate-treated animals did not show improved cartilage health compared with untreated operated rabbits, but a slightly anti-inflammatory activity was observed in the synovial membrane. Risedronate administration showed a slight tendency to increase subchondral bone plate thickness in lateral compartments but, it did not show conservation of periarticular bone and was not be able to suppress the osteophyte formation. In conclusion, long-term risedronate use did not demonstrate a positive effect on reducing the cartilage damage, and failed to prevent the subchondral bone changes and osteophytogenesis in an experimental rabbit model of OA.